THE EFFECTIVENESS OF “STUDENT QUESTION” LEARNING STRATEGY TO STUDENT’S LEARNING OUTCOME IN ECOSYSTEM MATERIAL FOR STUDENTS IN X GRADE OF SENIOR HIGH SCHOOL - ISMIY NOER WAHYUNI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
One of learning strategies which can be done by teacher to surmount imbalance of right and left brain activity is using of learning strategy of student question. This research was conducted to describe effectiveness of “student question” learning strategy to the student’s learning outcome. This research was conducted in three steps: preparing, implemantation, and analysis step. The research result showed that percentage of student which get value of learning outcome with predicate mastery about 80% and not mastery about 20%. Key words: Effectiveness, Student Question, Learning outcome, Ecosystem